Assisting Civics Teachers in Curriculum Innovation that Integrates Local Environmental Issues and Community Participation as a Context for Civics Learning - Dimyati, Endang; Islam, Nibras Shohwatul; Maulani, Mahfiroh Fitria; Anjani, Dewi Mega; Maulida, Milda (Fakultas Kewirausahaan Universitas Garut, 2025)
Integrating local issues into the Civics curriculum allows students to better connect with the realities around them. Issues such as environmental management, cultural diversity, and local social problems provide concrete examples that can be discussed in class. The mentoring training for Civics teachers was conducted through a collaborative approach that included the following steps: gathering information through surveys and discussions with Civics teachers to understand the challenges faced in implementing a curriculum that integrates local issues. The training results showed that the use of NLP tools, such as ChatGPT and other applications, helped students identify and correct errors in their writing. The success of the Civics teacher mentoring training in integrating local issues can serve as a model for other educational programs. The emphasis on collaboration between schools, communities, and local governments not only enriches students' learning experiences but can also lead to concrete solutions to existing social issues.